Obspack CH4 time-series result from Hyltemossa (150.0 m) - Michal Heliasz; Tobias Biermann; Meelis Molder; ICOS RI (Integrated Carbon Observation System, 2025)
This data file contains high accuracy European ObsPack observational timeseries in netCDF format of ambient mole fraction of ch4 in dry air collected at Hyltemossa (150.0 m). The measurements were calibrated using the WMO GAW calibration scale WMO X2004A. Included are (all whenever available) historical PI QCed data, ICOS Level 2 data, ICOS FastTrack data and ICOS NRT data. It is part of the 2025.3 FastTrack update of the Globalview EU CH4 data product and is intended for use in carbon cycle inverse modeling, model evaluation, and satellite validation studies. Metadata for the full ch4 product release are available at https://commons.datacite.org/doi.org/10.18160/3TB5-D6TM. Please also visit http://www.gml.noaa.gov/ccgg/obspack/ for more information. If you use these data in your research, please consider citing the full ObsPack release that this file is part of (https://commons.datacite.org/doi.org/10.18160/46ST-DEVK).
ICOS RI, Heliasz, M., Biermann, T., Molder, M. (2025). Obspack CH4 time-series result from Hyltemossa (150.0 m), 2016-12-13–2025-10-02, European ObsPack, https://hdl.handle.net/11676/Ojg0CoPV-ZHNuRWO_DNbLZwr
Keywords: Carbon Portal; CH4; ICOS; Obspack; WMO X2004A; atmospheric dry air ch4 mole fraction; time series; time instant, UTC; time instant, UTC; quality flag; quality flag; data level (Obspack); data level (Obspack); standard deviation of gas mole fraction; standard deviation of gas mole fraction; ICOS mole fraction uncertainty metrics; ICOS mole fraction uncertainty metrics; CH4 (dry air mole fraction); CH4 (dry air mole fraction); Oceanography, Hydrology and Water Resources; Oceanografi, hydrologi och vattenresurser; Meteorology and Atmospheric Sciences; Meteorologi och atmosfärsvetenskap; Physical Geography; Naturgeografi; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap